SINGULARIDADES DA MONTAGEM FOTOGRÁFICA EM FABIANA WIELEWICKI (Palíndromo, 2013)
This research approaches Fabiana Wielewicki's photographic production. The topics treated on her work were considered according to the following aspects: photography-artifice, photography-reveal, photography-enigma. Those aspects allow the artist to build her pictures engaging in a dialog with the photomontage technique, and making this technique  her main artifice.
Keywords: Fabiana Wielewicki; photography; photomontage